1982
DOI: 10.1172/jci110468
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identity of Human Histocompatibility Leukocyte Antigen-B27 Molecules from Patients with Ankylosing Spondylitis and Normal Individuals

Abstract: A B S T R A C T Although the association between human histocompatibility leukocyte antigen (HLA) B27 and ankylosing spondylitis is the prototype of HLAdisease association, the mechanism underlying these associations has not been determined. We have investigated the possibility that the B27 molecules from patients with ankylosing spondylitis are different from those of normals, and only the "different" molecules predispose the individual to disease. Biosynthetically radiolabeled HLA-B27 molecules from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Evidence in favor of structural identity of the B27 antigen in AS, RS and controls has been shown using monoclonal antibody (Grumet et al 1981). Studies using biosynthetically radiolabelled B27 molecules in AS and controls showed no difference by two-dimensional gel electrophoresis, and neither did [^H] argininelabelled tryptic and chymotryptic peptides of trypsin-insoluble material by reverse-phase high pressure liquid chromatography (Karr et al 1982). Evidence in favor of epitope similarity of the B27 antigen and certain bacteria has been the demonstration of cross-reactivity of klebsiella, shigella and yersinia antigens with determinants recognized by monoclonals B27M1 and -M2 (van Bohemen et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in favor of structural identity of the B27 antigen in AS, RS and controls has been shown using monoclonal antibody (Grumet et al 1981). Studies using biosynthetically radiolabelled B27 molecules in AS and controls showed no difference by two-dimensional gel electrophoresis, and neither did [^H] argininelabelled tryptic and chymotryptic peptides of trypsin-insoluble material by reverse-phase high pressure liquid chromatography (Karr et al 1982). Evidence in favor of epitope similarity of the B27 antigen and certain bacteria has been the demonstration of cross-reactivity of klebsiella, shigella and yersinia antigens with determinants recognized by monoclonals B27M1 and -M2 (van Bohemen et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the HLA-B27 molecule by two-dimensional gel electrophoresis [11] DNA sequencing [12] and restriction fragment length polymorphism [13] have all shown no molecular differences in this genetic marker between patients with AS and healthy controls. Furthermore, using HLA-B27 specific monoclonal antibodies, no disease-associated variant of HLA-B27 has been observed in AS [14].…”
Section: The Aetiological Role Of Hla-b27mentioning
confidence: 99%
“…However, such a polymorphism has not been detected in two studies using two-dimensional PAGE and tryptic and chymotryptic peptide mapping. 19 20 In fact no difference in structure of B27 was noted between subjects with AS and normal subjects. The polymorphism in B27 structure defined by B27m2 (12% of individuals typed as B27+ by conventional means lack the determinant detected by this monoclonal antibody) does not correlate with susceptibility to AS.'…”
Section: Discussionmentioning
confidence: 85%